Captopril suppresses hepatic mammalian target of rapamycin cell signaling and biomarkers of inflammation and oxidative stress in thioacetamide-induced hepatotoxicity in rats. (3rd September 2021) - Al-Hashem, Fahaid; Al Humayed, Suliman; Haidara, Mohamed A.; Abdel Latif, Noha S.; Al-Ani, Bahjat
Abstract: Background: The potential inhibitory effects of captopril, the angiotensin-converting enzyme inhibitor, on thioacetamide (TAA)-induced hepatic mammalian target of rapamycin (mTOR), liver injury enzymes, blood pressure, and biomarkers of inflammation and oxidative stress have not been investigated before. Materials and methods: Rats were either injected with TAA (200 mg/kg; twice a week for 8 weeks) before being sacrificed after 10 weeks (model group) or were pretreated with captopril (150 mg/kg) daily for two weeks prior to TAA injections and continued receiving both agents until the end of the experiment (protective group). Results: Captopril significantly ( p  < .05) inhibited TAA-induced hypertension, liver tissue levels of mTOR, TIMP-1, TNF-α, IL-6, MDA; and blood levels of lipids, ALT, and AST. We further demonstrated a significant ( p  < .01) positive correlation between mTOR scoring and the levels of inflammatory, oxidative and liver injury biomarkers. Conclusions: Captopril protects against TAA-induced mTOR, liver injury enzymes, dyslipidemia, hypertension, inflammation, and oxidative stress.